Transitions Into, and Through, Higher Education: The Lived Experiences of Students Who Identify as LGBTQ+ - Glazzard, Jonathan; Jindal-Snape, Divya; Stones, Samuel (Frontiers in Education, 2020)
This study explores the lived experiences of students who identify as lesbian, gay, bisexual, transgender or queer (LGBTQ+) during their transitions into, and through, higher education. Existing literature presents tragic narratives of students with LGBTQ+ identities which position them as victims. This study conceptualises transitions as complex, multiple and multi-dimensional rather than linear. The objectives of the study were to explore: the lived experiences of students who identify as LGBTQ+ in higher education; the role that sexuality and / or gender identity play in their lives over the course of their studies and LGBTQ+ students’ experiences of transitions into and through higher education. The study is longitudinal in design and draws on the experiences of five participants over the duration of a three-year undergraduate course in a university in the UK. Methods used include semi-structured interviews, audio diaries and visual methodologies to explore participants’ experiences of transitions. Data were coded and analysed thematically. This study uniquely found that the participants experienced multiple and multi-dimensional transitions during their time at university and that these transitions were largely positive in contrast to the mainly tragic narrative that is dominant within the previous literature. In addition, this is the first study to have explored the experiences of LGBTQ+ students using a longitudinal study design. This is the first study to apply the theory of multiple and multidimensional transitions (MMT) to participants in this context.